Peran Reputasi Penjual Skincare Online dalam Hubungan Review, Perceived Price, dan Niat Beli Konsumen Gen Z Pengguna Marketplace Shopee dan Lazada di Kota Semarang - Pramudita Nur Az-Zahra; Hanif Ahmadi (ARZUSIN, 2026)
Although the development of e-commerce has driven changes in consumer behavior, particularly among Generation Z in purchasing skincare products, the factors that most influence purchase intention remain a matter of debate, especially regarding the roles of online customer review, perceived price, and seller reputation. This study aims to analyze the effect of online customer review and perceived price on purchase intention, with seller reputation as a mediating variable. This study employed a quantitative approach with an explanatory research design, involving 100 Generation Z respondents who had purchased skincare products through a marketplace and were selected using purposive sampling. The data were analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The results showed that online customer review had a positive and significant effect on purchase intention and seller reputation. Meanwhile, perceived price had no significant effect on purchase intention, but it did affect seller reputation. This study also found that seller reputation had a positive effect on purchase intention and was able to mediate the relationship of online customer review and perceived price with purchase intention. These findings indicate that seller reputation is a key factor in increasing consumer purchase intention compared with price. Thus, this study contributes to strengthening the study of digital consumer behavior and provides practical implications that business actors need to focus on improving service quality and encouraging positive reviews in order to strengthen seller reputation and consumer trust.